PENDIDIKAN ISLAM DI PESANTREN - Muhammad Husni; Mudhofar (Pascasarjana Institut Agama Islam Al-Qolam, 2020)
Until now, the fact is that these kyai are intellectuals who have high creativity. They have such brilliant thoughts, feelings, ideas and experiences in developing learning developments in the traditional Islamic education tradition in Islamic boarding schools. Education in Islamic boarding schools is a pioneer for the progress of society. Besides that, it has a broad scientific capacity. This is proven by the many forms and models of learning in the pesantren and there is even a special curriculum for learning in the pesantren itself. aims to understand (1) how to take advantage of the wealth of classical Islamic scientific repertoire that Islamic boarding schools have as a means of responding to current problems while remaining inclusive in accepting changes for the better (2) developing the methodological aspects that the pesantren will run as one Islamic educational institutions. This research is a literature review with the hope of being able to track and prove the dynamics of Islamic development in Islamic boarding schools through the scientific transformation of the Islamic boarding schools.